2017
DOI: 10.1038/s41699-017-0011-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear graphene quantum capacitors for electro-optics

Abstract: Owing to its peculiar energy dispersion, the quantum capacitance property of graphene can be exploited in a two-dimensional layered capacitor configuration. Using graphene and boron nitride, respectively, as the electrodes and the insulating dielectric, a strongly nonlinear behavior at zero bias and small voltages is obtained. When the temperature is sufficiently low, the strong nonlinear interaction emerging from the quantum capacitance exhibits a diverse range of phenomena. The proposed structure could take … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 75 publications
(121 reference statements)
0
31
0
Order By: Relevance
“…where α is the contribution of JJs, and τ is the characteristic time of nonlinear interaction for the quantum capacitor [4]. This value has already been estimated theoretically [4] for a weakly nonlinear regime, which is not obviously a matter of interest in qubit design. The reason is that the anharmonicity should actually be large to guarantee two-level operation of the oscillator, strictly allowing no more than 1 photon at the qubit frequency ω to survive in the oscillator.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…where α is the contribution of JJs, and τ is the characteristic time of nonlinear interaction for the quantum capacitor [4]. This value has already been estimated theoretically [4] for a weakly nonlinear regime, which is not obviously a matter of interest in qubit design. The reason is that the anharmonicity should actually be large to guarantee two-level operation of the oscillator, strictly allowing no more than 1 photon at the qubit frequency ω to survive in the oscillator.…”
Section: Resultsmentioning
confidence: 75%
“…Since the limiting cases and truncated expansions may not be sufficiently accurate, the anharmonicity was studied with a completely numerical approach, where limiting expressions of the type reported in the previous study [4] no longer hold true and significantly deviate from exact values. The numerical computations are rather elaborate; therefore, instead of a description of the entire algorithm and minor details, the Mathematica calculation packages have been made freely available to readers as Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…For the BN thickness of 3nm to 70nm, the contribution of geometric parallel plate capacitance of the structure has been shown that can be neglected [2], and the quantum capacitance is given by…”
Section: Resultsmentioning
confidence: 99%
“…It is found that A rapidly increases with the temperature decreasing and also is a strong function of the capacitance area [1], and at temperatures of a few 0.1K easily yield strong nonlinearity. Signal can be fed into the qubit oscillator by inductive or capacitive coupling similar to the qubits based on JJs [2]. of or enhancement in the anharmonicity of A, leaving nonlinear terms of sixth and higher orders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation